Spectroscopic and Chromatographic Analysis of Some Commercial Samples of Neem Oil - Gunasekaran, S.; Renganayaki, V. (Asian Journal of Chemistry, 2010)
Pesticides have been in use right from the time mankind started agricultural practice. Since, both bio pesticides and synthetic pesticides have become indispensable in the field agriculture and industry. It has become imperative to characterize and to test the quality of pesticides used today. The present work encompasses the qualitative and quantitative analysis of commercial samples of neem oil-a biopesticide using FTIR spectroscopy and HPLC technique. Commercial cold pressed, solvent extracted and mechanical pressed neem oil samples have been analyzed using HPLC and the content of azadirachtin, the active pesticide component in neem oil has been determined. FTIR spectra of some commercial neem oil samples and azadirachtin have been recorded in the range 4000-400 cm-1. Samples of neem oil have been graded by comparing the internal standard ratio of the peaks corresponding to the specific modes of vibration of azadirachtin in the FTIR spectra.